Clinical Outcomes of Remote Ischemic Preconditioning Prior to Cardiac Surgery: A Meta‐Analysis of Randomized Controlled Trials. Issue 2 (20th February 2017) - Pierce, Brian; Bole, Indra; Patel, Vaiibhav; Brown, David L.
Abstract : Background: Multiple randomized controlled trials of remote ischemic preconditioning (RIPC) prior to cardiac surgery have failed to demonstrate clinical benefit. The aim of this updated meta‐analysis was to evaluate the effect of RIPC on outcomes following cardiac surgery. Methods and Results: Searches of PubMed, Cochrane, EMBASE, and Web of Science databases were performed for 1970 to December 13, 2015. Randomized controlled trials comparing RIPC with a sham procedure prior to cardiac surgery performed with cardiopulmonary bypass were assessed. All‐cause mortality, acute kidney injury (AKI), and myocardial infarction were the primary outcomes of interest. We identified 21 trials that randomized 5262 patients to RIPC or a sham procedureprior to undergoing cardiac surgery. The majority of patients were men (72.6%) and the mean or median age ranged from 42.3 to 76.3 years. Of the 9 trials that evaluated mortality, 188 deaths occurred out of a total of 4210 randomized patients, with 96 deaths occurring in 2098 patients (4.6%) randomized to RIPC and 92 deaths occurring in 2112 patients (4.4%) randomized to a sham control procedure, demonstrating no significant reduction in all‐cause mortality (risk ratio [RR], 0.987; 95% CI, 0.653–1.492, P =0.95). Twelve studies evaluated AKI in 4209 randomized patients. In these studies, AKI was observed in 516 of 2091 patients (24.7%) undergoing RIPC and in 577 of 2118 patients (27.2%) randomized to a sham procedure. RIPC did not result in a significant reduction in AKI (RR, 0.839; 95% CI, 0.703–1.001 [ P =0.052]). In 6 studies consisting of 3799 randomized participants, myocardial infarction occurred in 237 of 1891 patients (12.5%) randomized to RIPC and in 282 of 1908 patients (14.8%) randomized to a sham procedure, resulting in no significant reduction in postoperative myocardial infarction (RR, 0.809; 95% CI, 0.615–1.064 [ P =0.13]). A subgroup analysis was performed a priori based on previous studies suggesting that propofol may mitigate the protective benefits of RIPC. Three studies randomized patients undergoing cardiac surgery to RIPC or sham procedure in the absence of propofol anesthesia. Most of these patients were men (60.3%) and the mean or median age ranged from 57.0 to 70.6 years. In this propofol‐free subgroup of 434 randomized patients, 71 of 217 patients (32.7%) who underwent RIPC developed AKI compared with 103 of 217 patients (47.5%) treated with a sham procedure. In this cohort, RIPC resulted in a significant reduction in AKI (RR, 0.700; 95% CI, 0.527–0.930 [ P =0.014]). In studies of patients who received propofol anesthesia, 445 of 1874 (23.7%) patients randomized to RIPC developed AKI compared with 474 of 1901 (24.9%) who underwent a sham procedure. The RR for AKI was 0.928 (95% CI, 0.781–1.102; P =0.39) for RIPC versus sham. There was no significant interaction between the two subgroups ( P =0.098). Conclusions: RIPC does not reduce morbidity or mortality in patients undergoing cardiac surgery with cardiopulmonary bypass. In the subgroup of studies in which propofol was not used, a reduction in AKI was seen, suggesting that propofol may interact with the protective effects of RIPC. Future studies should evaluate RIPC in the absence of propofol anesthesia.